The Right to Dividends-Can Shareholders Still Receive Dividends in Case of Legal Dissolution? - Kevin Dembele (International Journal of Science and Society, 2022)
If the subject of dividend distribution is limited to what the dividends actually represent, there should be no room for uncertainty in the conversation. However, dividends, which are defined as a portion of a company's profit that belongs to each shareholder at the end of each financial year, in relation to the shares held by him, can raise new questions in many different respects. Not only can they raise questions about when they can be requested or who they belong to in the case of the transfer of shares (aspects to which the doctrine has already given an answer), but they can also raise questions about their situation in the event that the company is dissolved. As a result, the topic that is being discussed in this investigation is whether or not shareholders will have the opportunity to exercise their entitlement to dividends in the event that the corporation is dissolved by a court of law.